THE ISSUE OF CREATING A REPERTOIRE IN THE THEATERS OF UZBEKISTAN (ON THE EXAMPLE OF SURKHANDARYA REGIONAL MUSICAL DRAMA THEATER) - Faxriddin Abduvohidov (Galaxy International Interdisciplinary Research Journal, 2021)
The article discusses the views of the Surkhandarya Theater on the folk traditions of the theater, the experience gained, the results of research and various aspects of other theaters.